2015
DOI: 10.1186/s12911-015-0194-y
|View full text |Cite|
|
Sign up to set email alerts
|

Physicians’ responses to computerized drug interaction alerts with password overrides

Abstract: BackgroundAlthough evidence has suggested that computerized drug-drug interaction alert systems may reduce the occurrence of drug-drug interactions, the numerous reminders and alerts generated by such systems could represent an excessive burden for clinicians, resulting in a high override rate of not only unimportant, but also important alerts.MethodsWe analyzed physicians’ responses to alerts of relative contraindications and contraindications for coadministration in a computerized drug-drug interaction alert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…This alert fatigue results in a considerable override of DDI alerts. A study done in Japan showed physicians overrode DDI alerts at a high rate in computerized drug interaction alert system [18].…”
Section: Introductionmentioning
confidence: 99%
“…This alert fatigue results in a considerable override of DDI alerts. A study done in Japan showed physicians overrode DDI alerts at a high rate in computerized drug interaction alert system [18].…”
Section: Introductionmentioning
confidence: 99%
“…64 Furthermore, security policies or measures such as providing justification to override password before prescription completion and enforcing role-based access control for clinicians hinder the effective use of CDSS alert. 87…”
Section: Organizationmentioning
confidence: 99%
“…Three studies in primary care and in outpatient setting showed that deficiencies in organizational rules and security policies impede alert use, contribute to HIT failure, and disrupt workflow. 36,59,87 According to Zazove et al, 55 institutional rules prohibit clinicians from modifying the best practice alert (BPA) fonts, colors, and word placement to suit their personal needs. Another study reported that alerts display information that conflicts with the hospital policy and standard medication practices.…”
Section: Organizationmentioning
confidence: 99%
“…Following publication of our paper in BMC Medical Informatics and Decision Making [ 1 ], it was brought to our attention that we had used a slightly modified version of DIAS which had been originally developed by another group [ 2 ]. We inadvertently failed to include this paper in the reference list.…”
Section: Erratummentioning
confidence: 99%